Vigabatrin-induced MRI changes associated with extrapyramidal symptoms in a child with infantile spasms. Issue 5 (October 2015) - Schonstedt, Valeria; Stecher, Ximena; Venegas, Viviana; Silva, Claudio
Vigabatrin is an antiepileptic drug used for treatment of infantile spasms. We present a female patient with infantile spasms in treatment with vigabatrin who developed ataxic movements. MRI demonstrated a symmetrical pattern of thalamic and globi pallidi diffusion restriction. While these image features have been widely described to be related to the use of vigabatrin, this case highlights the development of movement disorders in association with MRI signal changes. Awareness of the reversible nature of this condition is reassuring for the treating team and avoids unjustified studies.